2018
DOI: 10.1037/ort0000307
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and rumination: Transdiagnostic factors involved in the relation between subjective social status and anxiety and depressive symptoms and disorders among economically disadvantaged Latinos in primary care.

Abstract: Latinos face striking physical and mental health disparities. One factor associated with such disparities is subjective social status, reflecting subjective ratings of social standing. Yet there is presently a lack of empirical information about the mechanisms underlying relations between subjective social status and anxiety and depressive symptoms and disorders among Latinos in community medical services that serve as focal catchment areas for assessment and intervention programming. The present investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
3
8
0
Order By: Relevance
“…Responses are rated on a 5-point Likert scale ranging from 0 (very little) to 4 (very much) and summed to a total score (ASI-3-total). The ASI-3 has been successfully used in past research in Argentina (Bogiaizian et al 2017) and other Spanish-speaking samples (Zvolensky et al 2014(Zvolensky et al , 2018b. In the present investigation, internal consistency was excellent for the global score (α = 0.91) as well as the sub-facets: physical (α = 0.90), social (α = 0.80), and cognitive (α = 0.90).…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Responses are rated on a 5-point Likert scale ranging from 0 (very little) to 4 (very much) and summed to a total score (ASI-3-total). The ASI-3 has been successfully used in past research in Argentina (Bogiaizian et al 2017) and other Spanish-speaking samples (Zvolensky et al 2014(Zvolensky et al , 2018b. In the present investigation, internal consistency was excellent for the global score (α = 0.91) as well as the sub-facets: physical (α = 0.90), social (α = 0.80), and cognitive (α = 0.90).…”
Section: Methodssupporting
confidence: 60%
“…Furthermore, since AS amplifies the affective response to somatic perturbation (Drahovzal et al 2006;Varela et al 2007), AS may be particularly important to the Latinx population. Consistent with this formulation, non-COVID-19 related research has found that AS is associated with greater anxiety (Zvolensky et al 2018b), depression (Zvolensky et al 2020b), stress (Viana et al 2020), posttraumatic stress (Zvolensky et al 2020d), pain (Bakhshaie et al 2019;Kauffman et al 2019), and substance use problems (Zvolensky et al 2020a) among Latinx adults. Work among trauma-exposed Latinx samples, which is likely relevant to the current COVID-19 pandemic, suggests that AS is associated both with elevated mental health complaints as well as acculturative stress (Zvolensky et al 2018a).…”
mentioning
confidence: 75%
“…One of the key features of TM is to consider the processes involved in the different emotional disorders (Belloch, 2012), from which several scientific studies were developed surrounding the role of these processes or common factors called transdiagnostic, such as positive (PA) and negative (NA) affect, intolerance of uncertainty and anxiety sensitivity, among others (e.g. Talkovsky & Norton, 2018;Zvolensky et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Schubert et al41 found in an experimental study that low SSS elevated depressive cognitions and rumination. Other studies reported that rumination next to anxiety sensitivity mediated the associations between SSS and anxiety and depressive disorders 23,42…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, we were restricted in our choice of potential mediators in the association between SSS and mental health. Recent research suggested that social contact,55 chronic negative affect,56 as well as rumination and anxiety sensitivity42 mediate the effect of SSS on mental health. Future research should consider additional mediating mechanisms.…”
Section: Discussionmentioning
confidence: 99%